Analysis of risk factors for papillary thyroid carcinoma and the association with thyroid function indicators - Liu, Jianning; Feng, Zhuoying; Gao, Ru; Liu, Peng; Meng, Fangang; Fan, Lijun; Liu, Lixiang; Du, Yang (Frontiers in Endocrinology, 2024)
Objective: This study aims to analyze the relationship between papillary thyroid carcinoma (PTC) and various factors. Methods: The study involved two groups-PTC patients and non-PTC controls.We utilized binary logistic regression and Least Absolute Shrinkage and Selection Operator (Lasso) regression for variable selection and risk factor analysis. Correlation analysis was performed using Spearman's rank correlation. The diagnostic value of thyroid stimulating hormone (TSH) levels for PTC was assessed using Receiver Operating Characteristic (ROC) curves. Results: PTC patients exhibited higher body mass index (BMI) (23.71 vs. 22.66, p<0.05) and TSH levels (3.38 vs. 1.59, p<0.05). Urinary iodine concentration (UIC) was an independent predictor of PTC (OR=1.005, p<0.05). The optimal TSH threshold for PTC diagnosis was 2.4 mIU/L [The Area Under the Curve (AUC)=67.3%, specificity=71.4%, sensitivity=70.1%]. TSH levels positively correlated with BMI (r=0.593, p<0.05) and UIC (r=0.737, p<0.05). Conclusions: UIC may be an independent predictor of PTC, and TSH levels have some diagnostic value for identifying PTC.